Dampak Penggunaan Media Sosial TikTok Terhadap Akhlak Peserta Didik di SMA Muhammadiyah 23 Jakarta - Muhammad Zikri; Muhammad Arifin Rahmanto (Journal on Education, 2024)
By combining advances in digital technology and the popularity of social media platforms, TikTok has become an integral part of teenagers' daily lives, including students at SMA Muhammadiyah 23 Jakarta. This study aims to identify the impact of TikTok usage on students' morality. The research employs a qualitative method with a phenomenological approach to explore the subjective experiences and perceptions of students and teachers regarding TikTok usage. The findings indicate that TikTok has a complex impact on students' morality. Negative effects include the use of inappropriate language, exposure to unethical content, and disruption of academic focus. Students tend to imitate inappropriate behaviors and spend hours watching and creating content on TikTok, leading to a decline in academic performance and classroom engagement. However, there are also positive effects, such as increased creativity and opportunities for interactive learning through educational content. This study highlights the importance of the role of teachers and parents in supervising and guiding students' use of social media.